1988
DOI: 10.1029/rs023i004p00647
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wind and temperature on the height limit of a radio acoustic sounding system

Abstract: Influences of the atmospheric wind and temperature profiles upon the maximum height in temperature measurement by using a radio acoustic sounding system (RASS) were studied. The RASS uses radar to receive echoes (RASS echoes) backscattered from periodic perturbations in the atmospheric refractive index produced by an incident acoustic pulse and to measure the atmospheric temperature from the local speed of sound which is derived from the Doppler frequency shift of the RASS echo signal. One of the important con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…However, RASS with a 50-MHz WPR, such as the MU radar in Japan (Matuura et al 1986;Tsuda et al 1989Tsuda et al , 1994Adachi et al 1993) and the Gadanki MST radar in India (Sarma et al 2008(Sarma et al , 2010, used the sound at about 100 Hz, which made it possible to measure atmospheric temperatures up to about 23 km, exceeding the tropopause. Furthermore, the height coverage of RASS was significantly determined by the effects of the background wind velocity on the propagation of acoustic waves (Masuda 1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, RASS with a 50-MHz WPR, such as the MU radar in Japan (Matuura et al 1986;Tsuda et al 1989Tsuda et al , 1994Adachi et al 1993) and the Gadanki MST radar in India (Sarma et al 2008(Sarma et al , 2010, used the sound at about 100 Hz, which made it possible to measure atmospheric temperatures up to about 23 km, exceeding the tropopause. Furthermore, the height coverage of RASS was significantly determined by the effects of the background wind velocity on the propagation of acoustic waves (Masuda 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Masuda (1988) employed ray-tracing in order to analyze the propagation characteristics of acoustic wavefronts, and showed that the normal condition depends largely on profiles of background temperature and horizontal wind velocity, as well as distance between radar and acoustic sources. In the case of LTR/ RASS observations, the LTR cannot always steer the beam in the windward direction, while the MU radar can.…”
Section: System Requirementsmentioning
confidence: 99%
“…If the wind flows from the direction to which the LTR cannot steer the beam, it is expected that the height coverage is severely reduced. Based on the discussions using ray-tracing of acoustic wavefronts for various wind conditions (Masuda 1988), we decided on the speaker positions as shown in Fig. 11.…”
Section: System Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For turbulence echo observations by the MU radar and LTR, the vertical beam and four oblique beams steered to north, south, east, and west direction were employed. The turbulence echo parameters for the MU radar and LTR were estimated every 162 seconds and 86 seconds, respectively, with a height resolution of 150 m. The beam directions for MU radar-RASS observations were determined from real-time ray-tracing of acoustic wave-fronts (Masuda 1988).…”
Section: The Simultaneous Observation Of the Mu Radar-rass And Ltr-rassmentioning
confidence: 99%